2020
DOI: 10.31699/ijcpe.2020.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Modifying an Equation to Predict the Asphaltene Deposition in the Buzurgan Oil Field

Abstract: Buzurgan oil field suffers from the phenomenon of asphaltene precipitation. The serious negatives of this phenomenon are the decrease in production caused by clogging of the pores and decrease in permeability and wettability of the reservoir rocks, in addition to the blockages that occur in the pipeline transporting crude oil. The presence of laboratories in the Iraqi oil companies helped to conduct the necessary experiments, such as gas chromatography (GC) test to identify the components of crude oil and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This equation may be changed to produce outcomes that are similar to the test data since the sum of the experimental data and the sum of the CII inputs both equal 100 [16]. Raad and Ayad Al-haleem [21] used the MCII model to investigate the asphaltene stability of crude oil samples from Buzurgan oil field. After comparing the MCII value to the previous study of this oil field, they found that it confirms the problem of asphaltene deposition in this oil field, demonstrating the accuracy of this equation in predicting asphaltene precipitation and providing more reliability to be used in subsequent studies.…”
Section: Modified Colloidal Instability Index (Mcii)mentioning
confidence: 99%
“…This equation may be changed to produce outcomes that are similar to the test data since the sum of the experimental data and the sum of the CII inputs both equal 100 [16]. Raad and Ayad Al-haleem [21] used the MCII model to investigate the asphaltene stability of crude oil samples from Buzurgan oil field. After comparing the MCII value to the previous study of this oil field, they found that it confirms the problem of asphaltene deposition in this oil field, demonstrating the accuracy of this equation in predicting asphaltene precipitation and providing more reliability to be used in subsequent studies.…”
Section: Modified Colloidal Instability Index (Mcii)mentioning
confidence: 99%
“…This study discusses the removal of metals from the residual fraction using a relatively solvent extraction method. The solvents used are (n-hexane, light naphtha, and n-heptane) in this study, different solvent/oil ratios (4/1, 8/1, 10/1, 12/1, and 15/1), different perceptual periods (15,30,60,90, and 120 min) and different temperatures (30, 45, 60 and 90 ° C).…”
Section: -Experimental Workmentioning
confidence: 99%
“…The high levels of metal of petroleum residues currently need expensive improvements, both by high hydrogen adjustment costs and by high carbon discharge losses. If metal was extracted before the conventional hydrocracking process in a pretreatment stage, the residues could be improved more economically [14,15].…”
Section: -Introductionmentioning
confidence: 99%